Community-acquired pneumonia in the childhood: analysis of the diagnostic methods - Requejo,Henry I. Z. (2007)
Immunological assays such as CIE, LA, and Dot-ELISA were compared in order to diagnose community-acquired pneumonia. Serum, pleural fluid and urine samples were comparatively employed for bacterial antigen detection. Dot-ELISA proved to be an original and practical alternative procedure for detecting bacterial polysaccharide antigens from pleural fluid and/or concentrated urine samples, providing a rapid diagnosis for pediatric patients with community-acquired pneumonia.